An illustration of changing paradigms in water resource management in South Africa - Kearns, Nicholas Charles (Department of Environmental and Geographical Science, 2015)
This research studies the characteristic features of shifting paradigms in South African Water legislation over the past hundred years and aligns these changes in legislation with established world views in water resource management. A comparative analysis is used to describe and compare how changes in South African water legislation over the past century have changed water resource management paradigm and vice versa. Three distinct legislative periods are explored within South African water law. The first period from 1912 to 1955 was dominated by the Irrigation and Conservation of Waters Act of 1912 which favoured the agri-industrial and minority landowners. The second period is recognised as the pre-modernism and industrial modernism as paradigms that are closely aligned to the earliest national water legislation. It is characterised by the advancement of the hydraulic mission and growing demand for water resources. The third phase is the National Water Act which transformed water resource management in South Africa. It represents a radical shift in legislation from the dominant paradigm in South Africa and provides one of strongest features indicating that legislation, along with political will, is the major driver and enabler in contributing towards change in water resource management. In South Africa, the paradigm shift in water resource management is the direct result of legislative influence driven by a quest to emphasise the need for social justice and equity in order to redress an unjust Apartheid system.